Flipped Learning: An Innovation in Education for the 21st Century (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Today's education is heavily based on technology. Advances in technology have shaped the current education system. Flipped learning pedagogy is one of the most important educational technological discoveries of the 21st century. In the flipped classroom, students are given digital materials before the lesson, students try to understand the concepts and doubts arise, the teachers solve them during the following lesson activities. This study discusses the concept of flipped learning, the four pillars of flipped learning, the theoretical basis of flipped learning, its effectiveness and the positive and negative aspects of flipped learning.